Beyond the Classroom Walls: How Environment Shapes Academic Success in Kwara State - Adeseko Sunday Olaifa; Habeeb Olufemi Jimoh; Oba Baba Ayoku; Amdalat Abiodun Sagaya (Universitas Nurul Jadid, 2025)
This study investigated the relationship between environmental factors and student academic achievement in public high schools in Kwara State, Nigeria. The background of this study is the low national exam results and the need to understand the influence of class sizes, school facilities, peer interaction, and parental involvement on learning outcomes. This study uses a correlational type descriptive survey design with a sample of 300 students from 20 schools selected in stages. The instruments used include questionnaires on environmental factors and proforma WAEC exam results in Mathematics and English subjects (2019–2023). Data analysis was carried out with descriptive statistics and Pearson correlation at a significance level of 0.05. The results showed that students' academic achievement in the two core subjects was relatively high. There is a positive and significant relationship between environmental factors—especially class sizes and school facilities—and students' academic achievement. This study emphasizes the importance of conducive learning conditions, adequate educational facilities, and optimal class sizes in supporting academic success. It is recommended that policymakers and education stakeholders give priority to improving environmental aspects to support sustainable learning outcomes.